Mathematical models for prediction of water evaporation and thermal degradation kinetics of potato starch nanoparticles obtained by nanoprecipitation (2018)
The aim of this research is to study the thermal degradation kinetics andsome physicochemical properties of starch nanoparticles (SNPs) producedfrom potato starch (PS) by nanoprecipitation. Native PS is used as a control.The powder samples are analyzed by means of light and transmissionelectron microscopies, X-ray diffraction, Fourier transform infrared, andthermogravimetric analysis. PS shows oval and spherical granular shapedwith a diameter between 6 and 18mm, whereas SNPs display spherical andelliptical shapes with particle sizes between 50 and 150 nm. The relativecrystallinity is 25.4% to PS, and it decreases to approximately 23.5% forSNPs. Activation energy (E) associated to the water evaporation and thermaldegradation is calculated using the Newton model as well Ozawa-Flynn-Wall(OFW) and Kissinger-Akahira-Sunose (KAS) models, respectively. TheEvaluesusing the Newton model increase from 43.7 kJ mol 1(PS) to 84.1 kJ mol 1(SNPs). TheEvalues using the OFW and KAS models vary between 165 and227 kJ mol 1for PS, and between 180 and 400 kJ mol 1for SNPs. Modifica-tions inEvalues are associated with the increase in surface area in SNPs.This research reports new information of the thermal properties of SNPs